Characterization of tidal land for suitability of Arenga pinnata Merr. plant development - Helma Lia Gustina,; Besri Nasrul,; Idwar, (Jurnal Online Pertanian Tropik, 2025)
Sugar palm has an economic and ecological functions. Sugar palm is also able to adapt to marginal land including tidal. This study aims to identify land characteristics for their suitability for tidal. This land survey research was carried out in the Tenayan Raya, Pekanbaru. Sampling points are based on the overlay of land system maps, soil type maps and peat depth maps. Assessment of land suitability for palm trees is carried out using the limiting factor method in actual and potential conditions. The assessment results show that the actual land suitability of all SLH is not current suitable (N1) with the limiting factor for toxicity (xc), with very high Fe levels. Limiting factors of Fe can be overcome by water management, amelioration (supplement of organic material), liming and fertilization. Potential land suitability of all SLH is marginally suitable (S3).